HYDATID TORSION OF THE FALLOPIAN TUBE. DIAGNOSTIC DIFFICULTIES (CLINICAL CASE) - Сергей Валерьевич Рыбников; Светлана Ивановна Елгина; Игорь Сергеевич Захаров; Вадим Гельевич Мозес; Елена Владимировна Рудаева (The Publishing House Medicine and Enlightenment, 2019)
In the structure of acute gynecological diseases, the twisting of the uterine appendages is 7.0 %. The disease does not always have a typical clinical and laboratory picture and requires ultrasound examination in dynamics. With a further increase in the size of the organ or the presence of an adjacent formation, a change in the echostructure, hemodynamics in the appendages of the uterus, the growth of hydroperitoneum, the diagnosis of the twisting of the uterine appendages will be made. The examination will allow for timely surgery and will lead to the recovery of the patient. The present article describes a clinical case of torsion of the right fallopian tube hydatide in a 32-year-old woman. Given these features of the disease diagnosis of torsion had difficulties.